Use of compensatory strategies by trilingual speakers of typologically unrelated languages - Letica Krevelj, Stela (Array, 2009)
The present paper aims to explore the type and pattern of compensatory strategy use in the L3 production of multilingual speakers of three typologically unrelated languages. Preliminary results in this study corroborate the finding that previously acquired language systems in the multilingual speaker can be simultaneously activated during lexical search in the compensatory strategies (Jessner, 2006). However, none of factors discussed within the general context of conditioning cross-linguistic interaction seems to be able to account alone for the variation in the types of strategies used and language systems these strategies are based on. We propose that an interplay of a whole array of learner-, learning-, and word- based factors attribute to the patterns found in the type of strategy used, but also that the pattern is severely restricted by the level of multilinguals' metalinguistic awareness.The participants in the study were 30 Croatian L1 speakers studying English and Italian at Zagreb University who had fairly high levels of proficiency and fluency in both non-native languages as measured by an oral picture description task. Information on participants’ language learning background was obtained through a questionnaire which also elicited participants' perceived distance between the three languages. In order to get access to the use of compensatory strategies we used an oral translation task from L1 to L3 and, for a better insight into the impact of metalinguistic awareness, a stimulated recall interview was performed with a part of the sample to gauge the level of consciousness employed and the intentions underlying particular strategic behaviour.